Hubungan Antara Tindakan Bullying dengan Prestasi Belajar Anak Korban Bullying pada Tingkat Sekolah Dasar - Dwipayanti, Ida Ayu Surya; Indrawati, Komang Rahayu (Jurnal Psikologi Udayana; Vol 1 No 2 (2014)DO - 10.24843/JPU.2014.v01.i02.p04, 2014)
Violence action in school is getting widespreadly happened nowadays as can be seen from the growing number of news coverage about the acts of violence in newspaper or television. One example of acts of violence occurring in school is bullying. Bullying victim have a bad social adjustment so that it makes victim feel afraid to go to school even worse they don’t want to go at all, secede their selves out from the society, therefore later will be impact to academic achievement of the bullying victim. The aim of this study is to understand whether there is any correlation between bullying action and academic achievement.   This study is a quantitative research located in Badung Regency, Gianyar Regency and Denpasar City. Samples used in this study are 176 within clusion criteria those are elementary school students on grade 4th, 5th, and 6th, and are bullying victim. The sampling method is cluster sampling. Data collection method is questionnaire which measure bullying action that happened to bullying victim (validity is around 0.204 to 0.646 and its reliability is 0.926)  and the report score of uneven semester from bullying victim.   The analysis method is simple linear regression. From the statistic result the score of r = -0.779 and p = 0.000 (p less than 0.05) which means there is a negative correlation between bullying action and academic achievement of bullying victim at the elementary school level. The bullying victims will have trouble in social activities, feeling afraid of school that causes a high frequency of absent and can’t studying well, and have a trouble in concentration of study. It will impact to the academic achievement. The result of this study is show that there is a difference of bullying action to boys and girls.   Keywords      : bullying action, academic achievement, elementary school student